1995
DOI: 10.1103/physrevlett.75.4094
|View full text |Cite
|
Sign up to set email alerts
|

Hall Resistance in the Hopping Regime: A "Hall Insulator"?

Abstract: The Hall conductivity and resistivity of strongly localized electrons at low temperatures and at small magnetic fields are obtained. It is found that the results depend on whether the conductivity or the resistivity tensors are averaged to obtain the macroscopic Hall resistivity. In the second case the Hall resistivity always diverges exponentially as the temperature tends to zero. But when the Hall resistivity is derived from the averaged conductivity, the resulting temperature dependence is sensitive to the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 9 publications
4
23
0
Order By: Relevance
“…However, in experiments, the resistivity is measured in the zero-frequency limit at finite T and then the results are extrapolated to the T → 0 limit. It has been shown that for the conventional theory of variable-range hopping ρ xy → ∞ as T → 0, although this divergence is much slower than the divergence of ρ xx (39). This suggests the possibility that the "break" in the Hall resistance at ρ xy ðH p c Þ marks the transition from a bosonic Hall insulator to a more conventional Anderson insulator.…”
Section: Discussionmentioning
confidence: 99%
“…However, in experiments, the resistivity is measured in the zero-frequency limit at finite T and then the results are extrapolated to the T → 0 limit. It has been shown that for the conventional theory of variable-range hopping ρ xy → ∞ as T → 0, although this divergence is much slower than the divergence of ρ xx (39). This suggests the possibility that the "break" in the Hall resistance at ρ xy ðH p c Þ marks the transition from a bosonic Hall insulator to a more conventional Anderson insulator.…”
Section: Discussionmentioning
confidence: 99%
“…Such a dependence is generated, in fact, by the Holstein process. 20,22 This is the basic reason why the Holstein process furnishes an explanation for the Hall effect in (localized) insulators. The adaptation of the Holstein idea to transitions between two leads with continuous energy spectra is actually simpler than the original model, in which an additional phonon is needed to conserve energy.…”
Section: Principles Of Decoherencementioning
confidence: 99%
“…͑A6͒ gives the nonlocal corrections to it, which result from interference. 4,5 That is, the current in the jl bond is affected by the voltage drops on the kl and jk bonds.…”
Section: ͑A1͒mentioning
confidence: 99%
“…This countercurrent has been related to the dc Hall effect in insulators. 5 The study of the orbital magnetic response to a timedependent flux 6,7 is of interest by itself, and also because it is relevant to experiments 8 designed to detect persistent currents in mesoscopic rings. 9 Nonequilibrium magnetization may be used to measure specific electronic relaxation rates.…”
Section: Introductionmentioning
confidence: 99%